(untitled) (Global Journal of Human-Social Science, 2013)
This study examines the development and the implementation of the Malay medium of instruction policy in the Malaysian educational system and the relation of this policy to Fishman s model and a multilingual society The study uses interviews with persons directly involved in the process of education in Malaysia and examines a number of scholarly publications and other primary sources of information Historical study is chosen as the research design As a plural society Malaysia considers nation building or national integration Ibrahim 1986 as being of the utmost importance Fishman 1968 developed the concept of nationalist-nationist functions of language in nation building Since independence the Malaysian leadership has believed that education is critical for national integration It is generally believed that schools inculcate children with values and knowledge that are supportive of a national ideology The present study focuses on the process of developing and implementing the Malay medium of instruction policy in Malaysia The performance of Malay-medium of instruction universities National University of Malaysia UTM and UPM at the post-graduate level is impressive These universities have proven their ability to get Master s and Ph D degree holders and medical specialists from overseas and local universities There have been thousands of Malay-language theses in science from public universities after 1990 which indirectly shows that the Malay language can be used in education in a manner that is world class